Os santos dos caminhos portugueses - Marques, José (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present study, developed by invitation of the Scientific Commission of the VII Jacobean Congress, held in Santiago de Compostela, from the 16th to the 18th of October 2004, presents a global view of the main Portuguese thaumaturge saints and their respective devotion centres, scattered through the routes more frequently travelled over by the Portuguese pilgrims, either they chose some of these sanctuaries as the exclusive goal of their pilgrimage or, on their way to Compostela, they took the opportunity to visit them and plead their patron saints for protection. We have given precedence to the reports of the many and diversified “miracles” obtained by Portuguese devotees, but, although rare, we have also listed some miracles operated in favour of pilgrims from abroad, who had come on purpose to supplicate for their desired grace to be conceded. The combined news of these Portuguese thaumaturge saints and of the miracles operated in the centres where they were venerated helps to understand the subject, still rather unknown, of popular devotion in Medieval Portugal.